PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI POWTOON UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA SD. - Barokah, Awalina; Lestari, Nabilah Ayu (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
Abstract: this study aims to determine the influence interactive learning media based powtoon on the cognitive learning outcomes. This study used experimental research with a nonequivalent comparison-group design. The population of this study was class V SD with sample was class VA of 23 student who were treated with interactive learning media based powtoon and student class VB which totaled 28 students with no treatment using interactive learning media based powtoon. Data collection was carried out with a test of cognitive learning outcomes that had been tested for validity and reliability. Data analysis using Univariate Analysis of Variance with 5% of significance level. The results showed that the difference in the average score of the post test class VA was 86,21 while the average post-test score class VB was 73.57. Interactive learning media based powtoon has a significant and positive effect on the cognitive learning outcomes seen from the calculation of 53,67 and P of 0.000; P=0.000<0.05;